Desempenho operacional de duas enfardadoras de fardos prismáticos retangulares no palhiço de cana-de-açúcar - Gomes, Anderson Ravanny de Andrade [UNESP] (2014)
The cultivation of sugar cane is one of the most important economic activities in Brazilian history. Mechanized harvesting of sugar cane was implanted due to economic, operational and environmental issues. Thus the remaining material of mechanized harvest oper ations can cause problems as the incidence of pests and difficult to control accidental and criminal. The use of available waste in the field by the gathering and bundling of this material provides new energy sources for industry. This work aimed to study the operational performance of two prismatic baling machines in the straw of sugarcane in company agricultural in São Miguel dos Campos - AL. The machines were evaluated in three different volumes of straw pickup, by regulating the accumulator of straw for each defined volume of straw. Were evaluated, fuel consumption, weight of bales, mineral impurities and moisture from the bales, distance height and width of the windrows, time and distance refers to the production of each bale, baling operational capabil ity. The results show that the Machine 2 has obtained higher density bales compared to Machine 1. The M achine 1 presented less fuel consumption. However, the Machine 2 produced the highest quantity of bales per hour. There were no significant differences w ith respect to mineral impurities in bales in three different volumes accumulation of straw. The operational field capacity in all treatments analyzed, was better for Machine ...